Preparation of Sepiolite Nanofibers Supported Zero Valent Iron Composite Material for Catalytic Removal of Tetracycline in Aqueous Solution - Han, Xiaoyu; Zhang, Hong; Zhang, Caihong; Zhao, Yan; Zhang, Na; Liang, Jinsheng (Frontiers in Chemistry, 2021)
The heavy use of antibiotics in medicine, stock farming and agriculture production has led to their gradual accumulation in environmental media, which poses a serious threat to ecological environment and human safety. As an efficient and promising catalyst for the degradation of antibiotics, nanoscale zero valent iron (nZVI) has attracted increasing attention in recent years. In this study, sepiolite nanofiber supported zero valent iron (nZVI/SEP) composite was prepared via a facile and environmental-friendly green method. The spherical nZVI particles (with size of 20-60 nm) were dispersed evenly on the surface of sepiolite nanofibers, and the catalytic performance for the removal of tetracycline hydrochloride (TC-HCl) in aqueous system was investigated. The eﬀect of nZVI loading amount, catalyst dosage, H2O2 concentration and pH on the removal efficiency of TC-HCl were studied. It revealed that the sepiolite supporter effectively inhibited the agglomeration of nZVI particles and increased the contact area between contaminant and the active sites, resulting in the higher catalytic performance than pure nZVI material. The TC-HCl removal efficiency of nZVI/SEP composite was up to 92.67% when TC-HCl concentration of 20 mg/L, catalyst dosage of 1.0 g/L, H2O2 concentration of 1.0 mM, pH value of 7. Therefore, the sepiolite nanofiber supported zero valent iron composites possess high catalytic activity for TC-HCl removal and have great application prospects in antibiotic wastewater treatment.